Pregnancy outcome after multifetal pregnancy reduction of triplets to twins versus reduction to singletons. Issue 3 (March 2020) - Zemet, Roni; Haas, Jigal; Bart, Yossi; Barzilay, Eran; Zloto, Keren; Argaman, Natan; Schwartz, Noa; Weisz, Boaz; Yinon, Yoav; Mazaki-Tovi, Shali; Lipitz, Shlomo
Abstract: Research question: Does fetal reduction of triplet pregnancies to singleton result in superior obstetric and neonatal outcomes compared with triplets reduced to twins? Design: A historical cohort study including 285 trichorionic and dichorionic triplet pregnancies that underwent abdominal fetal reduction at 11–14 weeks in a single tertiary referral centre. The study population comprised two groups: reduction to twins ( n = 223) and singletons ( n = 62). Main outcome measures were rates of pregnancy complications, preterm delivery and neonatal outcomes. Non-parametric statistical methods were employed. Results: Triplet pregnancies reduced to twins delivered earlier (36 versus 39 weeks, P < 0.001) with higher prevalence of Caesarean section (71.1% versus 32.2%, P < 0.001) compared with triplets reduced to singletons. Preterm delivery rates were significantly higher in twins compared with singletons prior to 37 weeks (56.9% versus 13.6%, P < 0.001), 34 weeks (20.2% versus 3.4%, P = 0.002) and 32 weeks (9.6% versus 0%, P = 0.01). No significant difference was found in the rate of pregnancy loss before 24 weeks (1.3% in twins versus 4.8% in singletons, P = 0.12) or in the rate of intrauterine fetal death after 24 weeks (0.4% versus 0%, P = 1.0). Both groups had comparable obstetrical complications and neonatal outcomes, except for higher rates of neonatal intensive care unit admission in twins (31.9% versus 6.8%, P < 0.001). Conclusions: Reduction of triplets to singletons rather than twins resulted in superior obstetric outcomes without increasing the procedure-related complications. However, because the rate of extreme prematurity in pregnancies reduced to twins was low, the overall outcome of those pregnancies was favourable. Therefore, the option of reduction to singletons should be considered in cases where the risk of prematurity seems exceptionally high.